Sedimentación de plataforma interna-externa con desarrollo de montículos en el Viseense del sector central de la Sierra de la Estrella (Carbonífero, Córdoba) - Mas, R.; Moreno Gonzalez, I.; Rodríguez Martinez, M.; Rodríguez, Sergio (Coloquios de Paleontología, 2000)
Late Viséan calcareous rocks containing buildups occur in the Sierra de la Estrella, Guadiato Valley. Bioclastic, breccioid and biohermal limestones as well as sandstones 1 Depto y UEI de Paleontología, Facultad de Ciencias Geológicas e Instituto de Geología Económica (CSIC-UCM). Ciudad Universitaria. 28040 Madrid. 2 Depto de Estratigrafía y UEI de Correlaciones Estratigráficas y Paleogeografía, Facul tad de Ciencias Geológicas e Instituto de Geología Económica (CSIC-UCM). Ciudad Universitaria. 28040 Madrid. 9 M. Rodríguez, et al. Sedimentación de plataforma interna-externa con desarrollo... and conglomerates occur. Lithofacies analysis allow to identify 7 types, with 9 characteristic microfacies: 1.Micropeloidal mudstone-wackestone with stromatactoid cavities and fenestral fabrics, 2.Algal-bioclastic wackestone-packstone, 3.1.Pseudopeloidal packstone, 3.2.Packstone with algae, pseudopeloids and lithoclast, 4.1.Bryozoal-crinoidal packstone, 4.2.Packstone with algae and sponge spiculae, 5.Packstone-rudstone with lithoclasts, 6.Cortoid-lithoclasts grainstone, 7.Hybrid sandstones. Sediments are attributed to a inner to outer carbonate ramp with sporadic terrigenous influence. Some microbial mounds developed in such environment.